The Experience of Couples in the Process of Treatment of Pathological Gambling: Couple vs. Individual Therapy - Tremblay, Joël; Dufour, Magali; Bertrand, Karine; Blanchette-Martin, Nadine; Ferland, Francine; Savard, Annie-Claude; Saint-Jacques, Marianne; Côté, Mélissa (Frontiers in Psychology, 2018)
Context. Couple treatment for pathological gambling is an innovative strategy. There are some results supporting its potential effectiveness, but little is known about the subjective experiences of the participants. Objective. The aim of this article is to document the experiences of gamblers and their partners participating in one of two treatments, namely individual or couple. Method. In a study aiming to evaluate the efficacy of the Integrative Couple Treatment for Pathological Gambling (ICT-PG), couples who were entering specialized treatment for the addiction of one member who was a pathological gambler were randomly assigned to individual or ICT-PG. Nine months after their admission to treatment, gamblers and partners (n=21 couples; n=13 ICT-PG; n=8 individual treatment) were interviewed in semi-structured interviews. A sequenced thematization method was used to extract the major themes. Results. This study highlighted five major themes in the therapeutic process noted by the gamblers and their partners mainly after the couple treatment but also partly through the individual therapy. These were: 1) the gamblers’ anxiety about having to reveal their gambling problems in couple therapy; 2) the wish to develop a mutually beneficial understanding of gambling and its effects on the partners in the two types of treatments; 3) the transformation of negative attributions through a more effective intra-couple communication fostered by the couple therapy; 4) the partners’ contribution to changes in gambling behaviour and prevention of relapses, which were both better supported in couple therapy; and 5) the interpersonal nature of gambling and its connections with the couples’ relationship. However, gamblers who were in individual treatment were more likely to mention that their partners’ involvement was not necessary. Participants likewise made a few recommendations about the conditions underlying the choice of one treatment method or the other. Discussion. Participants reported satisfaction with both treatment models, but their experiences was more positive in couple treatment. Complementary benefits emerged from each form of treatment, which points to future treatments involving both types. Future research should explore both the couple processes associated with attempts to stop pathological gambling and the various ways of involving partners in the gamblers’ treatment.